The ways to increase the durability of cutting tools (sintered carbide knives) in the production of steel fiber - F. M. Novikov; Yu. I. Kozyreva (Литьë и металлургия)
One of the ways to increase the strength and reliability of building structures is the use of steel – fibre reinforced concrete. Steel – fibre reinforced concrete has significant advantages over conventional concrete. A high degree of resistance to cracking contributes to an increase in such physical and mechanical parameters as compressive, tensile and bending strength, water resistance, frost resistance, resistance to water and chemical penetration. In steel – fibre reinforced concrete, steel – fibre is used as a reinforcing material, evenly distributed over the volume of concrete.In the process of steel – fibre production, the fiber is cut with carbide knives. The article deals with the issues of increasing the wear resistance of carbide knives used for cutting steel – fibre, and suggests ways to increase the durability of cutting tools. The influence of the quality of tungsten-cobalt hard alloy on the wear resistance of knives is analyzed, and a knife attachment device is developed.